Bond behavior of stainless steel wire ropes embedded in engineered cementitious composites. (26th April 2021) - Li, Ke; Liu, Weikang; Zhang, Kai; Wang, Xinling; Zhu, Juntao; Sheikh, Shamim
Highlights: Bond behavior of HSSS wire ropes in ECC was studied experimentally. Influence laws of various parameters on bond behavior were revealed. A bond-slip model was developed for HSSS wire ropes embedded in ECC. Abstract: Engineered cementitious composites (ECC) feature high post-cracking resistance and ductility. The stainless steel wire rope meshes have been successfully used to restore or increase capacity of existing structures. By combining the advantages of these two materials, an innovate jacketing of ECC reinforced with high-strength stainless steel (HSSS) wire rope meshes are expected to significantly improve structural performance while used for repair or strengthening of existing structures. To understand the bond behavior of HSSS wire ropes embedded in ECC, experimental studies were conducted by using direct pull-out specimens. Test variables consisted of nominal diameter of HSSS wire rope, embedded length and strength of ECC. The failure mechanism and bond-slip characteristics of HSSS wire ropes in ECC were investigated. Based on analyses of test results, the effects of the test variables on the bond properties of HSSS wire ropes embedded in ECC were revealed. A bond-slip model and the expressions of the model parameters were developed for charactering the bond-slip relationship between HSSS wire ropes and ECC.